Urinary Stone Disease The Practical Guide to Medical and Surgical Management - Stoller, Marshall L.; Meng, Maxwell V.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Urinary stone disease has afflicted mankind for centuries and continues to be a significant medical ailment throughout the world. Contemporary management reflects the changes and evolution that have occurred in both medicine and, specifically, urology. Traditional open surgery has been nearly replaced by minimally invasive techniques, the result of technologic innovations, miniaturization of instruments, and interdisciplinary collaboration. Nevertheless, nephrolithiasis remains a chronic disease and our fundamental understanding of the pathogenesis, and molecular and genetic basis of stones as well as their prevention, remains rudimentary. All large calculi were once small calculi. Where do stones originate and what facilitates their retention, allowing them to grow? Although we rely on 24-hour urinary collections, clearly our current methods of directing medical therapy have limitations. In addition, interest in disease prevention continues to grow and understanding basic questions and the underlying pathophysiology of stone disease will help optimize management strategies. Future advances in urinary stone disease will be the result of collaboration among urologists, nephrologists, radiologists, dieticians, scientists, and partners in industry. Physicians must not be complacent with the current status quo or be overly eager to intervene because techniques are less invasive; rather, the goals should be a better understanding of the underlying disease process in order to identify those at risk, prophylax against stone development and recurrence, and improved nonsurgical therapies.
Background -- Stone Nomenclature and History of Instrumentation for Urinary Stone Disease -- Epidemiology and Incidence of Stone Disease -- The Genetics of Stone Disease -- Theories of Stone Formation -- Structure and Compositional Analysis of Kidney Stones -- Metabolism -- Calcium Physiology -- Management of Patients With Hyperoxaluria -- Renal Acid-Base Balance and Renal Tubular Acidosis -- Urinary Stone Inhibitors -- Modulators of Crystallization of Stone Salts -- Hormonal Influences on Nephrolithiasis -- Associated Systemic Diseases -- Medical Evaluation of Stone Disease -- Pharmacologic Prophylaxis of Calcium Stones -- Diet and Urolithiasis -- Uric Acid Urolithiasis -- Struvite Stones -- Cystine Stone Disease -- Urinary Stones of Unusual Etiology -- Presentation and Evaluation -- Imaging of Urinary Stone Disease -- Physician Safety -- Treatment of Acute Renal Colic -- Anatomical Considerations in Urinary Stone Disease -- Treatment -- Conservative Management of Ureteral Calculi -- Ureteral Stents -- Anesthetic Considerations for Extracorporeal Shockwave Lithotripsy Percutaneous Nephrolithotomy, and Laser Lithotripsy -- Complications of Urinary Stone Surgery -- Extracorporeal Shockwave Lithotripsy -- Indications and Outcomes of Ureteroscopy for Urinary Stones -- Ureteroscopy -- Percutaneous Nephrolithotomy -- Percutaneous Nephrolithotomy -- Open Stone Surgery -- Laparoscopic Approach to Urinary Stone Disease -- Stones of the Urethra, Prostate, Seminal Vesicle, Bladder, and Encrusted Foreign Bodies.
Keywords: Urology; Surgery; Nephrology; Internal medicine; Urology; Surgery; Nephrology; Internal Medicine